Method for detecting copper particles in positive electrode powder

By adding the optimized concentration of dispersant NP-40 and using a copper indicator to the positive electrode powder of the battery for detection, the problem of low detection efficiency of copper impurities in the positive electrode powder of the battery is solved, efficient and accurate detection and removal are achieved, and the safety and performance stability of the battery are improved.

CN119757330APending Publication Date: 2025-04-04ZHEJIANG ZEEKR INTELLIGENT TECH CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510005191.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-04
Patent Text Reader

Abstract

The invention provides a method for detecting copper particles in positive electrode powder, and relates to the technical field of batteries. The method comprises the steps that a first mixed solution containing a dispersing agent NP-40 is added into positive electrode powder, stirring is conducted for 10-30 min, a second mixed solution is obtained, and the concentration of the NP-40 in the first mixed solution is 0.5 wt%-1 wt%; sieving the second mixed solution by using a screen to obtain an oversize product; ultrapure water is used for flushing oversize products, and impurities entering the suction filtration device along with water flow are collected through filter paper; drying the filter paper, and carrying out copper color development determination on impurities by using a copper indicator; the color developing filter paper is placed under quantitative analysis equipment to be analyzed, and the number of the color developing copper particles on the unit area and the mass fraction of copper in the copper particles are obtained. By adding the dispersing agent mixed solution with the optimized concentration, the agglomeration phenomenon of the positive electrode powder is effectively reduced, and the risk of screen blockage is reduced, so that the screening speed is increased, and the detection efficiency of the copper particles in the positive electrode powder is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a method for detecting copper particles in positive electrode powder. Background Art

[0002] With the global emphasis on environmental protection and safety, the market demand for lithium iron phosphate batteries has increased year by year due to their high safety and long cycle life. However, in the preparation and improvement of the battery positive electrode powder, some metal impurities such as iron, copper, chromium, nickel, etc. are often introduced. These impurities may be reduced to metal elements during the charging and discharging process of the battery, and then pierce the diaphragm, resulting in a poor K value of the battery cell, seriously affecting the production progress and performance of the battery. For magnetic metal impurities such as iron and nickel, they can usually be removed by physical adsorption through a demagnetizer. However, for non-magnetic particulate impurities such as copper, they need to be detected and handled separately at a later stage.

[0003] In the related art, the positive electrode powder is usually screened by dry screening or wet screening to obtain the sieve material; then, the sieve material is qualitatively colored to detect the copper particle content, but the detection efficiency is low. Summary of the invention

[0004] The present application provides a method for detecting copper particles in positive electrode powder, so as to improve the detection efficiency of copper particles in positive electrode powder.

[0005] In a first aspect, the present application provides a method for detecting copper particles in a positive electrode powder, comprising:

[0006] (1) adding a first mixed solution containing a dispersant NP-40 to the positive electrode powder and stirring for 10 min to 30 min to obtain a second mixed solution, wherein the concentration of NP-40 in the first mixed solution is 0.5 wt% to 1 wt%;

[0007] (2) sieving the second mixed liquid using a sieve to obtain a sieve-surface material;

[0008] (3) using ultrapure water to rinse the material on the sieve, and collecting impurities that flow into the suction filtration device with the water using filter paper;

[0009] (4) drying the filter paper and performing copper colorimetric determination of impurities on the filter paper using a copper indicator;

[0010] (5) placing the colored filter paper under a quantitative analysis device for analysis to obtain the number of colored copper particles per unit area and the mass fraction of copper in the copper particles. The quantitative analysis device includes at least one of an optical microscope, a Phenom electron microscope, and a scanning electron microscope-energy dispersive spectrometer (Scanning Electron Microscope with Energy Dispersive Spectroscopy, referred to as SEM-EDS).

[0011] In an optional embodiment, in step (1), the concentration of NP-40 in the first mixed solution is 0.5 wt %, and the stirring time is 15 min.

[0012] In an optional embodiment, in step (1), the stirring speed is 800 r / min to 1000 r / min.

[0013] In an optional embodiment, in step (1), the second mixed solution includes 2 g NP-40, 800 ml ultrapure water and 100 g positive electrode powder.

[0014] In an optional embodiment, the sieve is 800-1200 mesh.

[0015] In an optional embodiment, the pore size of the filter paper is 3 μm-7 μm.

[0016] In an optional embodiment, the pore size of the filter paper is 5 μm.

[0017] In an optional embodiment, the positive electrode powder is selected from lithium iron phosphate material, and the lithium iron phosphate material satisfies any one of the following: 0.8μm≤D50≤1.8μm; 0.4μm≤D10≤0.6μm and 0.8μm≤D50≤1.8μm; 0.8μm≤D50≤1.8μm and 2.5μm≤D90≤5.5μm; 0.4μm≤D10≤0.6μm, 0.8μm≤D50≤1.8μm, 2.5μm≤D90≤5.5μm.

[0018] In an optional embodiment, the positive electrode powder is selected from lithium iron manganese phosphate material, and the chemical formula of lithium iron manganese phosphate material is LiMn x Fe 1-x PO4, where 0.2≤x≤0.8.

[0019] In an optional embodiment, the surface of the particles of the positive electrode powder comprises a carbon coating layer, and the mass fraction of the carbon coating layer is 0.1%-3%.

[0020] In an optional embodiment, the copper indicator is obtained by uniformly mixing liquid A and liquid B in a volume ratio of 1:1, liquid A is obtained by dissolving dicyclohexanone oxalyldihydrazone in anhydrous ethanol, and liquid B is obtained by dissolving sodium acetate and ammonium acetate in ultrapure water.

[0021] In an optional embodiment, before step (3), the method further includes: verifying the effectiveness of the copper indicator based on dust-free paper and copper-containing materials, wherein the copper-containing materials include copper foil, metallic copper and copper alloys.

[0022] The implementation of this application has at least the following beneficial effects:

[0023] 1) By adding a dispersant mixture of optimized concentration to the positive electrode powder, the agglomeration of the positive electrode powder during the screening process is effectively reduced, and the risk of screen clogging is significantly reduced, thereby speeding up the screening of the positive electrode powder and improving the detection efficiency of copper particles in the positive electrode powder;

[0024] 2) By using a copper indicator to perform colorimetric determination of impurities on the filter paper, and combining quantitative analysis equipment to perform quantitative and qualitative analysis of impurities on the filter paper, the number and mass fraction of copper particles can be accurately detected, thereby improving the accuracy and reliability of copper particle detection in the positive electrode powder;

[0025] 3) By combining rapid screening with efficient testing, manpower, time and material costs are reduced. By effectively detecting and removing impurities such as copper particles, it helps to troubleshoot production problems in the preparation and improvement of battery positive electrode powders, reduce the risk of poor K value in battery cells, and thus improve battery safety and performance stability. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In the related art, when the positive electrode powder is screened by dry screening or wet screening, lithium iron phosphate and lithium iron manganese phosphate particles are small in size and large in specific surface area, so they are prone to agglomeration and form large particles. The screen is easily clogged during the screening process, resulting in screening difficulties and reducing the screening speed of the positive electrode powder, thereby resulting in low detection efficiency of copper particles in the positive electrode powder, and increasing manpower, time and material costs.

[0028] Based on the technical problems existing in the related art, this application optimizes the concentration of dispersant NP-40 in wet screening, reduces the agglomeration of powder during the screening process, and fully considers the manpower, time and material costs to determine the optimal NP-40 concentration and stirring time, thereby accelerating the screening speed of positive electrode powder and improving the detection efficiency of copper particles in positive electrode powder.

[0029] The present invention provides a method for detecting copper particles in positive electrode powder, comprising the following steps:

[0030] (1) adding a first mixed solution containing a dispersant NP-40 to the positive electrode powder and stirring for 10 min to 30 min to obtain a second mixed solution, wherein the concentration of NP-40 in the first mixed solution is 0.5 wt% to 1 wt%; wherein NP-40 is a nonionic surfactant that can reduce the surface tension of the liquid and help disperse solid particles; the dispersant is fully mixed and acts on the powder particles by stirring, so that the powder particles are evenly distributed in the mixed solution, thereby forming a stable suspension; illustratively, the stirring time can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min, 40 min, 41 min, 42 min, 43 min, 44 min, 45 min, 46 min, 47 min, 48 min, 49 min, 50 min, 51 min, 52 min, 53 min, 54 min, 55 min, 56 min, 57 min, 58 min, 59 min, 60 min, 61 min, 62 min, 63 min, 64 min, 65 min, 66 min, 67 min, 68 min, 69 min, 70 min, 71 min, 72 min, 73 min, 74 min, 75 min, 76 min, 77 min, 78 min, 79 min, 80 min, 81 min, 82 min, 83 min, 17min, 18min, 19min, 20min, 21min, 22min, 23min, 24min, 25min, 26min, 27min, 28min, 29min, 30min or any two thereof, and the concentration of NP-40 in the first mixed solution can be 0.5wt%, 0.55wt%, 0.6wt%, 0.65wt%, 0.7wt%, 0.75wt%, 0.8wt%, 0.85wt%, 0.9wt%, 0.95wt%, 1wt% or any two thereof. By adding the mixed solution containing NP-40 to the positive electrode powder and stirring for 10min-30min, the dispersibility of the positive electrode powder is effectively improved, and good dispersibility helps to prevent the powder from forming large particles during the screening process, thereby reducing the risk of screen blockage, making the screening process smoother, and increasing the screening speed of the positive electrode powder, thereby improving the detection efficiency of copper particles in the positive electrode powder.

[0031] (2) The second mixed liquid is sieved using a sieve to obtain an oversize material; the larger particles are separated from the smaller particles by the physical separation effect of the sieve, wherein the oversize material is mainly composed of larger particles and incompletely dispersed powder particles, and due to the effect of the dispersant, the powder particles are less agglomerated, so that the sieving process can be carried out more smoothly.

[0032] (3) The material on the sieve is rinsed with ultrapure water, and impurities entering the filtration device with the water flow are collected through filter paper; by using ultrapure water to rinse the material on the sieve, fine particles and impurities attached to the surface can be effectively removed, ensuring that the collected impurities do not contain unnecessary interferences, and further through the filter paper and the filtration device, the impurities in the water flow are effectively collected on the filter paper, providing samples for subsequent color development detection.

[0033] (4) Drying the filter paper and using a copper indicator to perform a copper colorimetric determination on the impurities on the filter paper; by drying the filter paper, it is possible to ensure that the impurities do not contain moisture, thereby improving the accuracy of the colorimetric reaction; by using the copper indicator to chemically react with the copper particles on the filter paper, a visible color change can be produced, thereby visualizing the location and quantity of the copper particles.

[0034] (5) placing the colored filter paper under a quantitative analysis device for analysis to obtain the number of colored copper particles per unit area and the mass fraction of copper in the copper particles, wherein the quantitative analysis device includes at least one of an optical microscope, a Phenom electron microscope, and a scanning electron microscope-energy spectrometer.

[0035] In one implementation, the quantitative analysis device is any one of an optical microscope, a Phenom electron microscope, and a scanning electron microscope-energy spectrometer, for example, the quantitative analysis device is an optical microscope. For example, by observing the color filter paper with an optical microscope and quantitatively analyzing the number of copper particles per unit area, preliminary particle distribution information, such as particle distribution position, shape, and number, can be provided; further, by using an optical microscope for more precise analysis, the elemental composition and mass fraction of the copper particles can be accurately determined, and quantitative and qualitative data can be provided, which is convenient for verifying the purity and content of the copper particles.

[0036] In another implementation, the quantitative analysis device is any combination of an optical microscope, a Phenom electron microscope, and a scanning electron microscope-energy spectrometer, etc. For example, the quantitative analysis device is a combination of an optical microscope and an electron microscope-energy spectrometer. For example, by observing the color filter paper with an optical microscope and quantitatively analyzing the number of copper particles per unit area, preliminary particle distribution information, such as particle distribution position, shape, and number, can be provided; further, by using an electron microscope-energy spectrometer for more precise analysis, the elemental composition and mass fraction of the copper particles can be accurately determined, and quantitative and qualitative data can be provided, which is convenient for verifying the purity and content of the copper particles.

[0037] By adding a dispersant mixture of optimized concentration to the positive electrode powder, the agglomeration of the positive electrode powder during the screening process is effectively reduced, and the risk of screen clogging is significantly reduced, thereby accelerating the screening speed of the positive electrode powder and improving the detection efficiency of copper particles in the positive electrode powder; by using a copper indicator to perform colorimetric determination of impurities on the filter paper, and combining quantitative analysis equipment such as an optical microscope and a scanning electron microscope-energy spectrometer to perform quantitative and qualitative analysis of impurities on the filter paper, the number and mass fraction of copper particles can be accurately detected, thereby improving the accuracy and reliability of copper particle detection in the positive electrode powder; by combining rapid screening with efficient detection, manpower, time and material costs are reduced, and by effectively detecting and removing impurities such as copper particles, it is helpful to troubleshoot production problems in the preparation and improvement of battery positive electrode powders, reduce the risk of poor K values ​​in battery cells, and thus improve battery safety and performance stability.

[0038] In a preferred embodiment, in step (1), the concentration of NP-40 in the first mixed solution is 0.5 wt %, and the stirring time is 15 min.

[0039] In a specific embodiment, in step (1), the stirring speed is 800 r / min to 1000 r / min.

[0040] Exemplarily, the stirring speed can be 800r / min, 810r / min, 820r / min, 830r / min, 840r / min, 850r / min, 860r / min, 870r / min, 880r / min, 890r / min, 900r / min, 910r / min, 920r / min, 930r / min, 940r / min, 950r / min, 960r / min, 970r / min, 980r / min, 990r / min, 1000r / min or a range consisting of any two of them; a moderate stirring speed can provide sufficient shear force to help the dispersant act more effectively on the positive electrode powder particles, ensure that the particles are evenly dispersed in the mixed liquid, and reduce agglomeration; and this speed range, while providing effective dispersion, avoids the increased energy consumption and equipment wear that may be caused by excessively high stirring speed, and further optimizes the energy efficiency ratio of the operation.

[0041] In a preferred embodiment, in step (1), the second mixed solution includes 2 g NP-40, 800 ml ultrapure water and 100 g positive electrode powder.

[0042] Exemplarily, 2 g of NP-40 is dissolved in 800 ml of ultrapure water, 100 g of positive electrode powder is slowly added in batches, and stirred at a stirring speed of 900 r / min for 10 min to obtain a second mixed solution; the same magnet and stirring speed should be used during the stirring process to ensure consistent dispersion effect per unit time.

[0043] In a specific embodiment, the sieve is 800-1200 mesh.

[0044] Correspondingly, common sieves include low mesh sieves, medium mesh sieves and high mesh sieves. Among them, low mesh sieves are used to separate larger particles, generally 10 mesh or 20 mesh, etc.; medium mesh sieves are used to separate medium-sized particles, generally 100 mesh or 200 mesh, etc.; high mesh sieves are used to separate very fine particles, generally 400 mesh, 800 mesh or 1200 mesh, etc. Considering that the purpose of screening is to separate the positive electrode powder from the copper particle impurities in the above-mentioned second mixed liquid, the basis for selecting the mesh number of the sieve is that the positive electrode powder in the second mixed liquid can pass through, but the larger copper particle impurities cannot pass through. Therefore, in order to reduce the large particle copper impurities passing through the sieve during the screening process, the mesh number of the sieve should not be too low, so a high mesh number sieve is selected. Exemplarily, the sieve is 800 mesh, 850 mesh, 900 mesh, 950 mesh, 1000 mesh, 1050 mesh, 1100 mesh, 1150 mesh, 1200 mesh, or a range consisting of any two thereof.

[0045] In a specific embodiment, the pore size of the filter paper is 3 μm-7 μm.

[0046] Considering that the selection of the pore size of the filter paper should be to ensure that the positive electrode powder remaining on the screen can pass through the filter paper during the filtration process, the pore size of the filter paper should not be too small. Exemplarily, the pore size of the filter paper can be 3μm, 4μm, 5μm, 6μm, 7μm or a range consisting of any two of them. By selecting a suitable pore size of the filter paper, most of the positive electrode powder can pass through the filter paper, thereby avoiding the accumulation of positive electrode powder on the filter paper to affect the color development effect of copper particle impurities. At the same time, this pore size should also be small enough to effectively block larger copper particle impurities, thereby ensuring the accuracy of subsequent color development detection.

[0047] In a preferred embodiment, the pore size of the filter paper is 5 μm.

[0048] In a specific embodiment, the positive electrode powder is selected from lithium iron phosphate material, and the lithium iron phosphate material satisfies any one of the following: 0.8μm≤D50≤1.8μm; 0.4μm≤D10≤0.6μm and 0.8μm≤D50≤1.8μm; 0.8μm≤D50≤1.8μm and 2.5μm≤D90≤5.5μm; 0.4μm≤D10≤0.6μm, 0.8μm≤D50≤1.8μm, 2.5μm≤D90≤5.5μm.

[0049] Exemplarily, the positive electrode powder is selected from lithium iron phosphate material, and the D50 of the lithium iron phosphate material can be 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm or a range consisting of any two of them.

[0050] Exemplarily, the positive electrode powder is selected from lithium iron phosphate material, and the D10 of the lithium iron phosphate material can be 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm or a range consisting of any two thereof, and the D50 can be 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm or a range consisting of any two thereof.

[0051] Exemplarily, the positive electrode powder is selected from lithium iron phosphate material, the D50 of the lithium iron phosphate material can be 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm or a range composed of any two of them, and the D90 can be 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3.0μm, 3.1μm , 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4.0μm, 4.1μm, 4.2μm, 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm or a range of any two thereof.

[0052] Exemplarily, the positive electrode powder is selected from lithium iron phosphate material, the D10 of the lithium iron phosphate material can be 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm or a range consisting of any two thereof, and the D50 can be 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm or a range consisting of any two thereof, and the D90 can be 2.5μm, 2.6μm, 2.7 μm, 2.8μm, 2.9μm, 3.0μm, 3.1μm, 3.2μm, 3.3μm, 3.4μm, 3.5μm, 3.6μm, 3.7μm, 3.8μm, 3.9μm, 4.0μm, 4.1μm, 4.2μm , 4.3μm, 4.4μm, 4.5μm, 4.6μm, 4.7μm, 4.8μm, 4.9μm, 5.0μm, 5.1μm, 5.2μm, 5.3μm, 5.4μm, 5.5μm or any two of them.

[0053] Exemplarily, D99 of the lithium iron phosphate material is less than 10 μm; (D90-D10) / D50 of the lithium iron phosphate material can be 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8 or a range consisting of any two thereof; the lithium content of the lithium iron phosphate material can be 3.9wt%, 4.0wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt% or a range consisting of any two thereof; lithium iron phosphate The iron content of the material can be 32.4wt%, 32.5wt%, 32.6wt%, 32.7wt%, 32.8wt%, 32.9wt%, 33wt%, 33.1wt%, 33.2wt%, 33.3wt%, 33.4wt%, 33.5wt%, 33.6wt%, 33.7wt%, 33.8wt%, 33.9wt%, 34wt%, 34.1wt%, 34.2wt%, 34.3wt%, 34.4wt% or a range consisting of any two of them; the phosphorus content of the lithium iron phosphate material can be 18.2wt%, 18.3wt%, 18.4wt%, 18.5wt%, 18.6wt%, 18.7wt%, 18.8wt%, 18.9wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 31wt%, 32wt%, 33 %, 8.8wt%, 18.9wt%, 19wt%, 19.1wt%, 19.2wt%, 19.3wt%, 19.4wt%, 19.5wt%, 19.6wt%, 19.7wt%, 19.8wt%, 19.9wt%, 20wt%, 20.1wt%, 20.2wt% or a range consisting of any two of them; the carbon content of the lithium iron phosphate material can be 0.95wt%, 0.96wt%, 0.97wt%, 0.98wt%, 0.99wt%, 1.0wt%, 1.01wt%, 1.02wt%, 1.03wt%, 1.04wt%, 1.05wt%, 1.06wt%, 1.07wt%, 1.08 %, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.2wt%, 1.29wt%, 1.3wt%, 1.31wt%, 1.32wt%, 1.33wt%, 1.34wt%, 1.35 or any two thereof; the compacted density of the lithium iron phosphate material is greater than 2.50g / cm3 ; The tap density of lithium iron phosphate material can be 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 Or a range consisting of any two of them; the powder resistivity of the lithium iron phosphate material is less than or equal to 25Ω·cm; the specific surface area of ​​the lithium iron phosphate material can be 11.5m 2 / g, 12m2 / g, 12.5m 2 / g, 13m 2 / g, 13.5m 2 / g, 14m 2 / g, 14.5m 2 / g or a range consisting of any two of them; the water content of the lithium iron phosphate material is less than 800ppm; the pH value of the lithium iron phosphate material can be 9, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10 or a range consisting of any two of them; the residual lithium of the lithium iron phosphate material is less than or equal to 400ppm; the total content of sodium and potassium in the lithium iron phosphate material does not exceed 350ppm, the total content of calcium and magnesium does not exceed 300ppm, the total content of copper and zinc does not exceed 50ppm, the content of sulfur does not exceed 200ppm, the content of manganese does not exceed 200ppm, the magnetic substance does not exceed 500ppm, and the number of magnetic metal particles does not exceed 95pcs / kg; the first discharge specific capacity of the lithium iron phosphate material is greater than or equal to 156mAh / g, and the first coulomb efficiency is greater than or equal to 96%.

[0054] In a specific embodiment, the positive electrode powder is selected from lithium iron manganese phosphate material, and the chemical formula of lithium iron manganese phosphate material is LiMn x Fe 1-x PO4, where 0.2≤x≤0.8.

[0055] Illustratively, x may be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, or a range consisting of any two thereof.

[0056] In a specific embodiment, the surface of the positive electrode powder particles comprises a carbon coating layer, and the mass fraction of the carbon coating layer is 0.1%-3%.

[0057] Exemplarily, the surface of the particles of positive electrode powder such as lithium iron phosphate material and lithium iron manganese phosphate material includes a carbon coating layer, wherein the mass fraction of the carbon coating layer can be 0.1%, 0.3%, 0.8%, 1.2%, 2.0%, 2.5%, 3.0% or a range consisting of any two of them.

[0058] In a preferred embodiment, the copper indicator is obtained by uniformly mixing liquid A and liquid B in a volume ratio of 1:1, liquid A is obtained by dissolving dicyclohexanone oxalyl dihydrazone in anhydrous ethanol, and liquid B is obtained by dissolving sodium acetate and ammonium acetate in ultrapure water. It should be noted that the present embodiment describes only an example of making a copper indicator. In practical applications, the selected copper indicator includes but is not limited to dicyclohexanone oxalyl dihydrazone, and can also be obtained commercially or synthesized by conventional methods in the art. The present embodiment does not limit the selected copper indicator.

[0059] In a specific embodiment, before step (3), the method further includes: verifying the effectiveness of the copper indicator based on dust-free paper and copper-containing materials, wherein the copper-containing materials include copper foil, metallic copper and copper alloys.

[0060] Hereinafter, the method for detecting copper particles in the positive electrode powder provided in the present application will be further introduced in combination with specific embodiments.

[0061] Unless otherwise specified, the reagents, materials and instruments used in the following examples are conventional reagents, conventional materials and conventional instruments in the art and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.

[0062] Example 1

[0063] This embodiment provides a method for detecting copper particles in positive electrode powder, and the detection method is as follows:

[0064] 1. Configuration of copper indicator

[0065] Weigh 0.2±0.01g of dicyclohexanone oxalyldihydrazone into a conical flask, add 100ml of anhydrous ethanol, stir in a 50°C heating furnace or on a hot plate until completely dissolved, transfer to a brown bottle after cooling, and mark it as liquid A; weigh 50.0±1g of sodium acetate and 20.0±1g of ammonium acetate into a conical flask, add 100ml of ultrapure water, stir in a 50°C heating furnace or on a hot plate until completely dissolved, transfer to a brown bottle after cooling, and mark it as liquid B; mix liquid A and liquid B in a volume ratio of 1:1 to obtain a copper indicator, and store it in a brown reagent bottle.

[0066] 2. Copper indicator effectiveness test

[0067] For example, take a small piece of dust-free paper and copper foil, add a few drops of copper indicator to ensure complete infiltration; let it stand for 5min-10min. If it is observed that the dust-free paper does not show blue but the copper foil shows blue, it means that the copper indicator is effective.

[0068] 3. Screening of positive electrode powder

[0069] Take 2g of dispersant NP-40 and dissolve it in 800ml of ultrapure water, slowly add 100g of lithium iron phosphate positive electrode powder in batches, stir at a stirring speed of 900r / min for 10min, slowly pour the stirred sample onto an 800-mesh sieve for sieving, and record the sieving time, where the sieving time is positively correlated with the degree of dispersion of the positive electrode powder; after sieving, use ultrapure water to rinse the bottom and edge of the sieve until only large particles of impurities remain on the sieve; use ultrapure water to rinse the large particles of impurities on the filter, and the impurities enter the filtration device through the water flow and are blocked on the 5μm nylon filter paper; record the number of impurity particles on the nylon filter paper; use tweezers to clamp the edge of the nylon filter paper and place it on dust-free paper, then transfer it to a 60℃ forced air drying oven and cover it with a petri dish to dry. Correspondingly, if the same concentration of dispersant is added to the same batch of positive electrode powder, the number of large particle impurities should be roughly the same after the same stirring time. Therefore, the degree of dispersion of the positive electrode powder can be judged based on the number of large particle impurities on the nylon filter paper.

[0070] 4. Copper color determination

[0071] Transfer the dried nylon filter paper to a glass plate or culture dish, use a dropper to take a small amount of copper indicator to fully soak the nylon filter paper, let it stand for 5-10 minutes, wait for the copper indicator to completely evaporate, and observe whether the material on the sieve turns blue to make a qualitative judgment.

[0072] 5. Copper particle observation

[0073] Place the colored nylon filter paper under an optical microscope for observation, and record the approximate position, shape and amount of the color. Use a scanning electron microscope-energy spectrometer to test the mass fraction of copper in the copper particles. And estimate the amount of copper impurities in the incoming material based on the number of blue dots in the sieve to quickly determine the degree of qualification of the incoming material.

[0074] Example 2

[0075] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Embodiment 1, except that during the screening of the positive electrode powder, the stirring time is 15 minutes.

[0076] Example 3

[0077] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Embodiment 1, except that during the sieving process of the positive electrode powder, the stirring time is 20 minutes.

[0078] Example 4

[0079] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Embodiment 1, except that during the screening of the positive electrode powder, the stirring time is 30 minutes.

[0080] Example 5

[0081] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Example 1, except that during the screening of the positive electrode powder, the amount of dispersant NP-40 added is 4 g.

[0082] Example 6

[0083] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Embodiment 5, except that during the screening of the positive electrode powder, the stirring time is 15 minutes.

[0084] Example 7

[0085] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Embodiment 5, except that during the screening of the positive electrode powder, the stirring time is 20 minutes.

[0086] Example 8

[0087] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Example 5, except that during the screening process of the positive electrode powder, the stirring time is 30 minutes.

[0088] Example 9

[0089] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Example 1, except that during the screening of the positive electrode powder, the amount of dispersant NP-40 added is 8 g.

[0090] Example 10

[0091] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Example 9, except that during the screening process of the positive electrode powder, the stirring time is 15 minutes.

[0092] Embodiment 11

[0093] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Embodiment 9, except that during the screening of the positive electrode powder, the stirring time is 20 minutes.

[0094] Example 12

[0095] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Embodiment 9, except that during the screening of the positive electrode powder, the stirring time is 30 minutes.

[0096] Embodiment 13

[0097] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Example 1, except that during the screening of the positive electrode powder, the amount of dispersant NP-40 added is 16 g.

[0098] Embodiment 14

[0099] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Example 13, except that during the screening of the positive electrode powder, the stirring time is 15 minutes.

[0100] Embodiment 15

[0101] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Example 13, except that during the screening process of the positive electrode powder, the stirring time is 20 minutes.

[0102] Example 16

[0103] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Example 13, except that during the screening of the positive electrode powder, the stirring time is 30 minutes.

[0104] Embodiment 17

[0105] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Embodiment 1, except that, during the screening of the positive electrode powder, the amount of positive electrode powder added is 120 g.

[0106] Embodiment 18

[0107] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Embodiment 1, except that, during the screening process of the positive electrode powder, the amount of positive electrode powder added is 150 g.

[0108] Embodiment 19

[0109] This embodiment provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Embodiment 1, except that, during the screening process of the positive electrode powder, the amount of positive electrode powder added is 300 g.

[0110] Comparative Example

[0111] This comparative example provides a method for detecting copper particles in positive electrode powder, which is basically the same as that of Example 6, except that no dispersant NP-40 is added during the screening of the positive electrode powder.

[0112] For example, the concentration of dispersant NP-40, stirring time, sieving time and the remaining large particle impurities on the filter paper in Examples 1-16 of the present application are shown in Table 1; the concentration of dispersant NP-40, stirring time, mass of positive electrode powder and sieving time in Examples 17-19 of the present application are shown in Table 2.

[0113] Table 1

[0114] project NP-40 concentration Stirring time (min) Sieving time(s) Large particles of impurities remain on the filter paper Example 1 0.25wt% 10min 29.73 many Example 2 0.25wt% 15min 15.36 More Example 3 0.25wt% 20min 13.37 More Example 4 0.25wt% 30min 12.10 less Example 5 0.5wt% 10min 23.39 less Example 6 0.5wt% 15min 10.92 few Example 7 0.5wt% 20min 10.49 few Example 8 0.5wt% 30min 9.78 few Example 9 1wt% 10min 15.77 less Example 10 1wt% 15min 10.21 few Embodiment 11 1wt% 20min 10.71 few Example 12 1wt% 30min 9.33 few Embodiment 13 2wt% 10min 14.38 less Embodiment 14 2wt% 15min 9.87 few Embodiment 15 2wt% 20min 9.17 few Example 16 2wt% 30min 8.86 few Comparative Example 0.5wt% 15min Cannot be sieved /

[0115] Table 2

[0116] project NP-40 concentration Stirring time (min) Positive electrode powder mass (g) Sieving time(s) Example 1 0.5wt% 15min 100g 10.92 Embodiment 17 0.5wt% 15min 120g 14.37 Embodiment 18 0.5wt% 15min 150g 53.79 Embodiment 19 0.5wt% 15min 300g 92.08

[0117] The following conclusions can be drawn from Table 1 and Table 2:

[0118] 1) From the NP-40 concentration, stirring time and the sieving time obtained in Examples 1-4 in Table 1, it can be seen that when the NP-40 concentration is constant, the sieving time is continuously reduced with the increase of stirring time, but when the stirring time is increased to 15 min, the reduction of the sieving time becomes less obvious, indicating that the dispersion effect has reached the best; this conclusion can also be drawn from Examples 5-8, Examples 9-12 and Examples 13-16 in Table 1.

[0119] 2) From the NP-40 concentration and stirring time in Examples 1, 5, 9, and 13 in Table 1 and the sieving time obtained therefrom, it can be seen that when the stirring time is constant, the sieving time gradually decreases with the increase of NP-40 concentration, but when the NP-40 concentration increases to 0.5wt%, the reduction in sieving time becomes less obvious, indicating that the dispersion effect has reached the best; this conclusion can also be drawn from Examples 2, 6, 10, 14 and Examples 3, 7, 11, 15 and Examples 4, 8, 12, and 16 in Table 1.

[0120] 3) From the comparison of Examples 2, 6, 10, 14 and the comparative example in Table 1, it can be seen that the addition of an appropriate concentration of NP-40 can significantly increase the possibility of positive electrode screening. This is mainly because NP-40 is a surfactant that can significantly reduce the agglomeration between lithium iron phosphate particles, prevent the generation of large particles, and avoid clogging the screen during screening.

[0121] 4) Based on the NP-40 concentration and stirring time in Examples 1-17 in Table 1 and the sieving time obtained therefrom, combined with the labor cost, time cost and material cost, it is preliminarily determined that the dispersant NP-40 has a better dispersing effect when the mass fraction is 0.5wt%, and 100g of the positive electrode powder can be evenly dispersed by stirring for 15min.

[0122] 5) From the NP-40 concentration, stirring time, amount of added positive electrode powder and the sieving time obtained in Table 2 Examples 1, 17-19, it can be seen that after determining the dispersant concentration to be 0.5wt% and the dispersion time to be 15min, the sieving time gradually increases with the increase of positive electrode powder, which indicates that the dispersion effect is gradually getting worse. When the concentration of the dispersant NP-40 is 0.5wt% and the dispersion time is 15min, the optimal sieving amount of the positive electrode powder is 100-120g.

[0123] In summary, by adding an appropriate amount of NP-40, the screening speed of the positive electrode material can be significantly improved, thereby improving the detection efficiency of copper particles in the positive electrode powder; when the NP-40 concentration is fixed, the screening time gradually decreases with the increase of stirring time, but after the stirring time reaches 15 minutes, the reduction is no longer significant, indicating that the dispersion effect has reached the best; similarly, when the stirring time is fixed, the screening time decreases with the increase of NP-40 concentration, but when the NP-40 concentration reaches 0.5wt%, the reduction is no longer significant, indicating that the dispersion effect at this time has reached the best; considering the labor, time and material costs, a 0.5wt% NP-40 concentration and a stirring time of 15 minutes can achieve a good dispersion effect, which is suitable for processing 100g to 120g of positive electrode powder.

[0124] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A method for detecting copper particles in positive electrode powder, characterized in that: include: (1) adding a first mixed solution containing a dispersant NP-40 to the positive electrode powder and stirring for 10 min to 30 min to obtain a second mixed solution, wherein the concentration of NP-40 in the first mixed solution is 0.5 wt% to 1 wt%; (2) sieving the second mixed liquid using a sieve to obtain a sieve-surface material; (3) washing the material on the sieve with ultrapure water, and collecting impurities that flow into the suction filtration device with the water using filter paper; (4) drying the filter paper and performing copper colorimetric determination of impurities on the filter paper using a copper indicator; (5) placing the colored filter paper under a quantitative analysis device for analysis to obtain the number of colored copper particles per unit area and the mass fraction of copper in the copper particles, wherein the quantitative analysis device comprises at least one of an optical microscope, a Phenom electron microscope, and a scanning electron microscope-energy spectrometer.

2. The method according to claim 1, characterized in that In step (1), the stirring speed is 800 r / min to 1000 r / min.

3. The method according to claim 1 or 2, characterized in that: In step (1), the second mixed solution includes 2g NP-40, 800ml ultrapure water and 100g positive electrode powder.

4. The method according to claim 1 or 2, characterized in that: The sieve is 800-1200 mesh.

5. The method according to claim 1 or 2, characterized in that: The pore size of the filter paper is 3 μm-7 μm.

6. The method according to claim 1, characterized in that The positive electrode powder is selected from lithium iron phosphate material, and the lithium iron phosphate material satisfies any one of the following: 0.8μm≤D50≤1.8μm; 0.4μm≤D10≤0.6μm and 0.8μm≤D50≤1.8μm; 0.8μm≤D50≤1.8μm and 2.5μm≤D90≤5.5μm; 0.4μm≤D10≤0.6μm, 0.8μm≤D50≤1.8μm, 2.5μm≤D90≤5.5μm.

7. The method according to claim 1, characterized in that The positive electrode powder is selected from lithium iron manganese phosphate material, and the chemical formula of the lithium iron manganese phosphate material is LiMn x Fe 1-x PO4, where 0.2≤x≤0.

8.

8. The method according to claim 6 or 7, characterized in that: The surface of the particles of the positive electrode powder comprises a carbon coating layer, and the mass fraction of the carbon coating layer is 0.1%-3%.

9. The method according to claim 1 or 2, characterized in that: The copper indicator is obtained by uniformly mixing liquid A and liquid B in a volume ratio of 1:1, wherein the liquid A is obtained by dissolving dicyclohexanone oxalyldihydrazone in anhydrous ethanol, and the liquid B is obtained by dissolving sodium acetate and ammonium acetate in ultrapure water.

10. The method according to claim 1 or 2, characterized in that: Before step (3), the method further includes: verifying the effectiveness of the copper indicator based on dust-free paper and copper-containing materials, wherein the copper-containing materials include copper foil, metallic copper and copper alloy.

Citation Information

Patent Citations

  • Lithium sulfur battery positive electrode paste preparation method

    CN108091839A

  • Method for detecting content of metal impurities in positive electrode material of lithium ion battery

    CN115096983A

  • Method for detecting content of metal elementary substance foreign matter particles in positive electrode active material

    CN118603703A

  • Method for detecting copper-containing nonmagnetic substance in positive electrode active material, method for controlling quality of copper-containing nonmagnetic substance in positive electrode active material, and method for detecting foreign matter in positive electrode active material

    CN118670960A

  • Simple detection method of metal

    JP2014052369A